A Qualitative Study on Experience of Stigma and Discrimination in Health Care Sector Among PLHA Attending VCTC Of New Civil Hospital and GSNP+ Of Surat - Bharat H Patel; Ratan K Srivastava; Rashmi Sharma; Mohua Moitra (National Journal of Community Medicine, 2016)
Introduction: Within health care settings, HIV-related stigma is a recognized barrier to access of HIV prevention and treatment services. The current study was undertaken with the objective to study various forms of stigma and discrimination towards PLHA in health care sector.